PENERAPAN KINERJA PROYEK KONSTRUKSI PADA Pembangunan Ruas Jalan dan Jembatan Tawang Ngalang Segmen IV menggunakan earned value concept - Kartika, Widya; Buddewi Sukindrawati; Diki Rohman (AGREGAT, 2024)
Implementation of construction projects to achieve planned goals requires project management. Accurate cost calculations, time calculations, and the quality of materials will influence the success of a construction project. Either method of controlling construction project costs and time is earned value concept method. A case study on the Tawang Ngalang Road and Bridge Segment IV construction project. Research method uses earned value concept method, which the method used to calculate the cost according to the budget and the work that has been completed or carried out. Analysis of project implementation performance in terms of cost and time by calculating the amount of BCWS, BCWP, and ACWP. Analysis of estimated costs and completion time for construction projects calculates CPI to-go and SPI to-go. The variables that will be investigated are Cost Variance (CV), Schedule Variance (SV), Cost Performance Index (CPI), and Schedule Performance Index (SPI). The research results show that overall, construction project is progressing well, with SPI results >1 indicating faster time than planned and CPI results >1 indicating more economical costs than budget. The SPI to-go value is 1.129, meaning the project was completed faster than planned. The CPI to-go value is 1.975, meaning the project implementation costs are lower than the planned budget. Based on the results of the evaluation and analysis of project implementation data with a positive deviation or 2.23% faster than the planned schedule